Strategi Peningkatan Kualitas Pelayanan Publik Berbasis Budaya Aparatur Sipil Negara “BerAKHLAK” pada Dinas Kependudukan dan Pencatatan Sipil Kota Bandung - Pranawa, Widyawan; Redjo, Samugyo Ibnu; Indrawati, Novie (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
This study aims to analyze strategies for enhancing public service quality based on cultural values of the State Civil Apparatus (ASN) ‘BerAKHLAK’ at the Department of Population and Civil Registration (Disdukcapil) of Bandung City during the 2021–2023 period. The background of this study is anchored in the introduction of the ASN core values ‘BerAKHLAK’ by President Joko Widodo, which constitutes a key component of the national bureaucratic reform agenda and the broader transformation of public-sector work culture. This study employs a qualitative method with a case study approach. It assesses how the Ber-AKHLAK values—service-oriented, accountable, competent, harmonious, loyal, adaptive, and collaborative—affect service quality. The theoretical framework employed in this study draws on Luthans’ organizational culture theory and Zeithaml’s public service quality model, which comprises five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Findings demonstrate that the Ber-AKHLAK values positively influence physical infrastructure, staff reliability, responsiveness, professionalism, and emotional engagement. However, challenges remain in consistency, behavior, and institutional integration. This study offers theoretical and practical insights into organizational culture transformation and public sector performance.